Why work-family conflict can drive your executives away? - Braun, Ana Cláudia (2018)
This study assessed the relationship between work-family conflict, work engagement, workaholism and turnover intention in business executives. 275 professionals (65.4% men) completed an online survey containing scales to assess work-family conflict, workaholism, work engagement and turnover intention. Descriptive and inferential statistics were conducted, as well as network and pathway analysis. Partial correlations between the workaholism dimension “working excessively” (WE) and work-family conflict (WFC) werer = .21. WE also predicted WFC (χ² = 26.24, df = 7, p < .001; CFI = .95; RMSEA = .10 (.06 - .14), particularly in terms of work interfering in family life, leading to higher turnover intention and reduced work engagement. Model estimates show variations according to gender.